The Effect of Emotional Freedom Technique Therapy on Nurse Burnout - Ni Made Nopita Wati; Ni Wayan Mirayanti; I Gede Juanamasta (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2019)
Burnout can develop as a result of long work stress and cause a change in attitudes and behaviors withdrawing psychologically. The most visible impact of burnout is the decline in performance and quality of service. As a result, they were unable to fulfill the work demands and finally decided not to attend, increasing rates of sick leave, reduced work effectiveness or even leaving their jobs. This study aims to determine the effect of Emotional Freedom Technique (EFT) therapy on burnout in implementing nurses. The design of this study uses quasi-experimental design with control group. The sample in the study were 38 nurses, divided into 2 groups, each group consisting of 19 people selected through purposive sampling. This study used the Wilxocon Signed Rank Test to determine the differences in one pre-post group and the Mann Whitney Test to analyze changes after two different post-post groups. The results showed the value of p value in the treatment group = 0,000 which means that there was an effect of therapy (EFT) on burnout in the implementing nurses, whereas in the control group there was no difference with the p value = 0.925, the p value was influenced by EFT therapy (Emotional Freedom Technique ) towards burnout of nurse nurses before and after in groups of 0,000. It is expected that the Hospital can overcome burnout by passing EFT therapy.